Energy and nutrient utilization in rice (Oryza sativa)-weed ecosystem under post emergence herbicide application - SONI, MONIKA; JAIN, K K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was carried out during 2010 and 2011 at the Research Farm of Krishi Nagar, J N Krishi Vishwa Vidyalaya, Jabalpur (Madhya Pradesh). The treatments consisted of weed control practices, viz. bispyribac sodium, penoxsulam, pyrazosulfuron-ethyl, cyhalofop-butyl + almix, fenoxaprop-p-ethyl + almix and control as main plot treatment and three day time application (morning, afternoon and evening) as sub plot treatment and laidout in split plot design in three replications. In rice (Oryza sativa L.)-weed ecosystem the solar energy utilization by weeds was maximum under control plot (836.46 and 786.52 lakh k cal/ha) where transplanting of crop was done without controlling of weeds, whereas pyrazosulfuron-ethyl treated plot registered lowest energy utilization (285.21 and 286.78 lakh k cal/ha) by weeds during both the years. The energy utilization by crop grain and straw was maximum with post emergence application of pyrazosulfuron-ethyl (527.83 and 533.65; 274.20 and 280.00 lakh k cal/ha). The studies on NPK removal by weeds and uptake by crop showed that the weed control treatments caused significant variations on these parameters. Application of pyrazosulfuron-ethyl also reduced the N (4.90 and 4.33 kg/ha), P (0.34 and 0.29 kg/ ha) and K (3.76 and 3.30 kg/ha) removal by weeds as compared to other herbicides and weedy check during both the years. The N (166.54 and 169.19 kg/ha), P (49.10 and 49.64 kg/ha) and K (170.95 and 173.13 kg/ha) uptake by crop was recorded higher with the application of pyrazosulfuron-ethyl. However, different day time application of post emergence herbicides was found statistically non-significant for energy and nutrient utilization by weeds and crop.